2016
DOI: 10.1080/01596306.2016.1183589
|View full text |Cite
|
Sign up to set email alerts
|

Policy critics and policy survivors: who are they and how do they contribute to a department policy role typology?

Abstract: This paper considers the policy 'roles' adopted by teachers enacting policy in a department. It draws on a longitudinal study of two secondary mathematics departments endeavouring to make deep change aligned with a demanding curriculum policy. The study validates aspects of an existing typology, demonstrates the existence of a variety of policy 'critics' and adds a category of 'survivor' teacher, showing the role can have considerable impact on enactment. The paper argues for an extension to a group construct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Furthermore, Ball et al's (2011aBall et al's ( , 2011b research revealed important fluidity, with school leaders and teachers playing differing roles over time and in relation to different kinds of policies, and thus engaging in various types of policy work. Other research has examined the complexities of enactment in schools (Alfrey et al, 2017;Golding, 2017;Woodcock & Hardy, 2019), teacher education (Lambert & O'Connor, 2018;Lambert & Penney, 2019), and sport coaching contexts (Hammond et al, 2019), with some authors extending the descriptors of actor roles to include survivor (Golding, 2017), initiator, disruptor, motivator, connector, change maker and innovator (Lambert & O'Connor, 2018), and provocateur (Lambert & Penney, 2019).…”
Section: Policy Enactment and Policy Actorsmentioning
confidence: 99%
“…Furthermore, Ball et al's (2011aBall et al's ( , 2011b research revealed important fluidity, with school leaders and teachers playing differing roles over time and in relation to different kinds of policies, and thus engaging in various types of policy work. Other research has examined the complexities of enactment in schools (Alfrey et al, 2017;Golding, 2017;Woodcock & Hardy, 2019), teacher education (Lambert & O'Connor, 2018;Lambert & Penney, 2019), and sport coaching contexts (Hammond et al, 2019), with some authors extending the descriptors of actor roles to include survivor (Golding, 2017), initiator, disruptor, motivator, connector, change maker and innovator (Lambert & O'Connor, 2018), and provocateur (Lambert & Penney, 2019).…”
Section: Policy Enactment and Policy Actorsmentioning
confidence: 99%
“…On the other hand, junior teachers tended to be receivers of policy, although there are indications that receivers might be far more widespread than this. In particular, the aforementioned finding elsewhere that teachers were agreeing to be involved in SSE for one school year on the basis that SSE would be passed on to another group of teachers once they had 'done their bit' for the school (O'Brien et al, 2019) further fuels our suspicion that policy receivers are perhaps more common than first theorised and then found in our data; or, maybe more appropriately, they might be what Golding (2017) has called policy-neutral 'survivors'. Particularly in the case of more experienced teachers, despite often demonstrating positivity and enthusiasm, it might be that they are actually passive and 'policy-resistant':…”
Section: Discussionmentioning
confidence: 62%
“…Thus, some staff members are narrators, some are transactors, some are enthusiasts and translators, but some are also receivers of policy, or policy survivors-and some can be combinations of roles. As others have found, positions can manifest and merge, cross and meld (Lambert & O'Connor, 2018), and teachers can adopt a predominant role or more than one role in relation to their enactment of policy (Golding, 2017). It is simply not possible for the staff body as a collective unit to respond to SSE in coherent and consistent ways, and instead, the complex and intricate policy work of various actors combine to make SSE happen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudonyms are used throughout. The study, and the associated enactment, is described more fully in Golding (2016).…”
Section: The Studymentioning
confidence: 99%